Rachel Carson’s enduring call: a 60-year echo for harmony with nature - Olcay Ünver; Gavrielle Orman; Kiril Hristovski (Academia Environmental Sciences and Sustainability)
Sixty years after Rachel Carson’s Silent Spring exposed some harmful effects of pesticides on species and ecosystems, this article examines the enduring relevance of her call for a more sustainable approach to agriculture. We explore pest management through three examples where significant improvements have been achieved. While the ongoing use of pesticides is far from the international goal of minimizing their impact, a beacon of hope emerges in the growing movement toward ecosystem-based solutions supported by science and international organizations. This article delves into the core principles of integrated pest management (IPM) and biopesticides, offering alternatives to traditional chemical insecticides. We showcase success stories from the citrus and apple industries, demonstrating significant reductions in synthetic pesticide use through the implementation of these methods. Additionally, the article explores Push–Pull technology, a powerful example from Kenya where habitat management effectively controls pests without harming the environment. By examining these advancements, we emphasize the progress made toward achieving better ecological balance in agricultural practices. This review aims to provide support for more sustainable agricultural practices, highlighting a few win–win relationships between farmers and nature.